The European Business excellence model and its improvement - Veselova, Andzela (University of Latvia, 2020)
Nowadays the practice of self-assessment is the strategy recommended by the EFQM Excellence Model for organizations aiming for improvement on organizational performance. Rigorous self-assessment helps large, small and medium companies work more efficiently, and it is a comprehensive, systematic and regular exercise for the evaluation of companies’ activities and results. Today’s customers have higher requirements than ever before. Therefore, in order to be competitive in the twenty first century, organizations need to improve continuously, meet the standards of excellence in quality and performance. One of the ways to achieve excellence is the use of Business Excellence Models. The aim of the research is to investigate the improvement possibilities of the performance quality assessment in Latvian enterprises basing on EFQM business excellence model. The hypothesis states that the improving of the EFQM business excellence model used in the performance quality assessment in Latvian companies by including important topical criteria and integrating them into conventional criteria of the model could drive the company to higher level of excellence. The tasks are the following: to study the principles of European business excellence model; to provide the assessment and verification the assumptions included in the EFQM business excellence model with author’s improvements by Latvian and foreign business excellence and quality experts; to draw the conclusions and make proposals.
Keywords: European Business excellence model; improvement; assessment; Research Subject Categories::SOCIAL SCIENCES::Business and economics